Multimodal ultrasound radiomics containing microflow images for the prediction of central lymph node metastasis in papillary thyroid carcinoma - Ben, Jiangyuan; Yv, Qiying; Zhu, Pengfei; Ren, Junhao; Zhou, Pu; Chen, Guifang; He, Ying (Frontiers in Oncology, 2025)
ObjectivesThis study aimed to construct a model by applying radiomics and machine learning (ML) to multimodal ultrasound images (including grayscale, elastography and microflow images) along with clinical data to predict central lymph node metastasis (CLNM) in patients with papillary thyroid cancer (PTC).MethodsA cohort of 213 patients who underwent thyroidectomy accompanied by lymph node dissection (LND) and were pathologically diagnosed with PTC postoperatively was enrolled and randomized to the training cohort (n = 170) or testing cohort (n = 43). Radiomics features were extracted from multimodal images and subsequently screened via the least absolute shrinkage and selection operator (LASSO). The same methods were applied to screen clinical features. Nine ML algorithms were used to construct clinical models, radiomics models and fusion models. Model performance was assessed via receiver operating characteristic curves (ROC), decision curve analysis (DCA), and Delong test. Finally, the optimal model was interpreted and visualized via Shapley additive explanation (SHAP).ResultsIn each modality, 1561 features were extracted from the ultrasound images. Sixteen features were ultimately retained, including 6 grayscale features, 6 elastography features, and 4 microflow features. From the clinical features, including gender, age, traditional ultrasound signs and serological indicators, 2 relevant features were selected. Among the prediction models, the fusion model constructed by Multilayer Perceptron (MLP) algorithm showed the best diagnostic performance, outperforming the other models in both the training cohort (AUC = 0.886) and the testing cohort (AUC = 0.873).ConclusionsThe fusion model based on clinical data and multimodal ultrasound radiomics has better predictive ability and net clinical benefit for CLNM in patients with PTC, confirms the diagnostic value of microflow images for CLNM, and can help to evaluate patients’ preoperative lymph node status and make the correct decision on the surgical procedure.